2005
DOI: 10.1080/0365510500208324
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid and apolipoprotein profiles in newborns and six‐year‐old children: The Tallinn Young Family Study

Abstract: Seventy children aged 6 years (34 boys, 36 girls) were studied for cardiovascular risk factors. Among the children 40 had also been investigated at birth. The aim of the study was to determine changes in serum lipoprotein parameters from birth up to preschool age and to assess the role of some relevant factors that might affect the process. An obvious association was found between serum apolipoprotein (apo) B levels, the apoB/apoA-I ratio and lipoprotein(a) (Lp(a)) levels at birth and at 6 years of age (r = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
5
0
1
Order By: Relevance
“…Since black–white differences in the ApoB/ApoA1 ratio, ApoB, and ApoA1 track during childhood and from adolescence to young adulthood [5860], they should protect against CVD in adult black women. Within this frame of reference, Lee et al have reported that the overall rate for fatal and nonfatal definite myocardial infarction was lower in blacks than in whites in the Community Cardiovascular Surveillance Program [61].…”
Section: Discussionmentioning
confidence: 99%
“…Since black–white differences in the ApoB/ApoA1 ratio, ApoB, and ApoA1 track during childhood and from adolescence to young adulthood [5860], they should protect against CVD in adult black women. Within this frame of reference, Lee et al have reported that the overall rate for fatal and nonfatal definite myocardial infarction was lower in blacks than in whites in the Community Cardiovascular Surveillance Program [61].…”
Section: Discussionmentioning
confidence: 99%
“…El grupo de edad de 9 a 10 años presentó diferencias estadísticamente significativas únicamente en la ApoB-100, con las concentraciones más bajas en el genotipo E; Kurvinen et al encontraron esta misma relación en niños de seis años (40). El efecto del polimorfismo de la ApoE únicamente sobre la apolipoproteína B-100 puede indicar el inicio de los cambios en las lipoproteínas que contienen esta apoliproteína como las LDL, VLDL y remanentes de lipoproteínas, lo que puede llegar a afectar el metabolismo lipídico desde muy temprana edad.…”
Section: Discussionunclassified
“…A higher intake of SAFA at 10-14 months and 15-18 months was associated with higher apo B/apo A-1 ratios, and a higher intake of MUFA and PUFA was associated with lower apo B/apo A-1 ratios at 4 years of age. To our knowledge, few studies have examined associations between dietary patterns and apo B/apo A-1 ratios (Kurvinen et al, 2005); more surveys should be performed. Another finding of our study was tracking of serum lipids from infancy to early childhood.…”
Section: Discussionmentioning
confidence: 99%